Deep Learning Based Techniques for Sentiment Analysis: A Survey - Etaiwi, Wael; Suleiman, Dima; Awajan, Arafat (Informatica, 2021)
The automated representation of human language using a number of techniques is called Natural Language Processing (NLP). Improvements to NLP applications are important and can be done using a variety of methods, including graphs, deep neural networks, and word embedding. Sentiment classification, which attempts to automatically classify opinionated text as positive, negative, or neutral, is a fundamental activity of sentiment analysis. Sentiment analysis methods focused on deep learning over the past five years are analyzed in this review